Study of phospholipid molecular species of the green seaweed \(Halimeda incrassata\) Lamx. from Truong Sa islands, Vietnam - Pham Thu, Hue; Nguyen Van, Tuyet Anh; Pham Quoc, Long; Le Tat, Thanh (Vietnam Journal of Marine Science and Technology, 2021)
In this report, by a high performance liquid chromatography (HPLC) - high resolution mass spectrometry (HRMS) method, 7 molecular species of phospholipid in the polar lipid class were identified including phosphatidylinositol (PI) and phosphatidylglycerol (PG). The PI 32:0 (16:0/16:0) and PG 34:3 (16:1/18:2) molecular species have the highest content. PI molecular species are mainly formed by saturated fatty acids (16:0, 18:0) and only one polyunsaturated fatty acids C20:4, while PG species are formed by unsaturated fatty acids (16:1, 18:2 and 18:3) and only one saturated fatty acid C16:0.